Grammarly Through the Lens of Student Perception - A'isyah Nurhidayah; Tatik Irawati (Jurnal Bahasa, Sastra, dan Studi Amerika, 2024)
Grammarly serves as an online grammar checker that allows users to identify and rectify errors in grammar, pronunciation, punctuation, and plagiarism. This study aims to explore students' perceptions regarding the use of Grammarly as a writing assistant in essay classes. Employing a qualitative case study approach, data were collected through questionnaires and structured interviews. The participants were English major students at Universitas PGRI Jombang enrolled in essay writing classes, with 23 students responding to the questionnaires and 4 participating in interviews. The findings indicate a positive perception among students towards Grammarly as a helpful tool for writing English essays. They appreciate its user-friendly interface, helpful advice, clear explanations, accurate grammar checks, and prompt corrections. Moreover, they find it beneficial for enhancing writing skills and boosting self-confidence, particularly in essay writing. The study also highlights Grammarly's role in facilitating learning about English grammar rules. Despite utilizing only the free version, nearly all students highly recommend Grammarly for supporting English students in essay writing. They value its straightforward feedback, which aids in understanding complex grammar issues and enables them to refine their writing while reducing common errors. In conclusion, students consider Grammarly a valuable tool for enhancing their essay writing skills. Not only does it assist in correcting grammatical errors, but it also serves as an educational resource that enriches students' understanding of English grammar. Therefore, integrating Grammarly into the essay writing curriculum can greatly benefit English students, providing them with an accessible and effective resource to improve their writing proficiency.